Aging in times of the COVID-19 pandemic: avoiding ageism and fostering intergenerational solidarity - Ayalon, Liat; Chasteen, Alison; Diehl, Manfred; Levy, Becca R; Neupert, Shevaun; Rothermund, Klaus; Tesch-Römer, Clemens; Wahl, Hans-Werner (The journals of gerontology. Series B, Psychological sciences, social sciences, 2021)
The COVID-19 pandemic has changed many aspects of the world, including how older persons are treated. We believe that research evidence from the behavioral sciences of aging can help address the pandemic in ways that can benefit the health and well-being of individuals across the life span.We think that there are three primary ways that evidence from behavioral sciences can make a difference. First, with the pandemic there has been a parallel outbreak of ageism. What we are seeing in public discourse is an increasing portrayal of those over the age of 70 as being all alike with regard to being helpless, frail, and unable to contribute to society. These views are being spread by social media, the press, and public announcements by government officials throughout the world (see Table 1 for examples). This is problematic for a number of reasons. Behavioral scientists know that older adults are an extremely heterogeneous group (Fingerman & Trevino, 2020). They differ in life experiences, cultural backgrounds, genetics, and health histories. Further, the process of aging itself is highly diverse and context-dependent; this is a fundamental insight of biological, behavioral, and social aging research (Kornadt & Rothermund, 2015; Wahl & Gerstorf, 2018). In addition, innumerable older persons defy the image of being frail and helpless, with countless older adults making valuable contributions to society (Corporation for National and Community Service, 2016; Diehl, Smyer, & Mehrotra, in press).
Advance access publication April 16, 2020
Gesehen am 02.07.2021